Pengaruh Model Pembelajaran P2RE dalam Meningkatkan Keterampilan Menulis Teks Berita Siswa Kelas XI SMA Rahmat Islamiyah Medan - Farell Zahra Vadinda; Faridah Faridah; Rina Devianty (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
The research that has been carried out is entitled "The Influence of the P2RE Learning Model in Improving the Ability to Write News Texts for class This research aims to improve the ability to write news texts through the P2RE (Preparation, Organizing, Reflective and Evaluation) learning model for class XI students at SMA Rahmat Islamiyah Medan. This research methodology is quantitative by producing a pretest and posttest. Research procedures include planning, implementing actions, observing and reflecting. Data collection techniques through non-tests (tests on student learning outcomes, observation, documentation and questionnaires). Data analysis includes data analysis of validity tests, reliability tests, normality tests, homogeneity tests, hypothesis tests. The results of the research revealed that the results of student learning observations at the pretest stage were 9.9%. At the stage of working on pretest questions individually the average score for students at XI SMA Rahmat Islamiyah Medan was only 76.2, while at the posttest stage student learning outcomes were 14.6% and at the posttest question stage as a group the students' average score was 89.33. So the conclusion is that the average student score increased after being given the P2RE learning model by 13,11.